Providing easier access to community‐based healthcare for people with joint pain: Experiences of delivering ESCAPE‐pain in community venues by exercise professionals. (10th August 2021) - Hurley, Michael; Sheldon, Helen; Connolly, Margaret; Carter, Andrea; Hallett, Rachel
Abstract: Background: Joint pain adversely impacts the physical, mental, socioeconomic and emotional wellbeing of many millions of people . Enabling Self‐management and Coping with Arthritic Pain using Exercise, ESCAPE‐pain, is a rehabilitation programme that reduces joint pain and its impact. The programme is usually delivered in clinical settings by physiotherapists but delivering it in community venues would improve access greatly. Aim: To explore the feasibility of delivering ESCAPE‐pain in community venues, and the experiences of organisations and facilitators delivering it. Methods: Semi‐structured interviews were conducted with managers of 17 community organisations and 10 facilitators. Results: People were happy to attend ESCAPE‐pain delivered by exercise professionals at community venues, which they found convenient and valuable. It expanded community organisation's offer to older people, utilised their facilities off‐peak and advanced facilitator's personal and professional development. Recruitment onto the programme was easiest where there were good links with local clinical providers. Although collecting outcome data was burdensome it demonstrated the programme's effectiveness to commissioners. Some clinical commissioners contracted community organisations to deliver ESCAPE‐pain reducing their costs and freeing up clinical facilities. Organisations also financed ESCAPE‐pain by charging participants a nominal fee for the programme, post‐programme classes to support participants remain active and/or a membership fee. Conclusions: ESCAPE‐pain delivered in community venues facilitated access to better care and on‐going support. Partnerships between healthcare commissioners and community providers maximised efficient use of their facilities and resources and fulfilled national policy of encouraging self‐management of long‐term conditions in the community.